Efficacy of ProTaper Retreatment System in Root Canals Obturated with Gutta-Percha Using Two Different Sealers and GuttaFlow - Siotia, Jaya (Hindawi Publishing Corporation, 2011)
Objective. To compare the efficacy of ProTaper retreatment files in removing three different obturating materials. Study Design. Forty-five human, single-rooted premolars were divided into three experimental groups. Group 1 was obturated with gutta-percha and AH Plus sealer, Group 2 was obturated with gutta-percha and zinc oxide eugenol sealer, and Group 3 was obturated with GuttaFlow. Retreatment was done using the ProTaper universal rotary retreatment files. Root halves were visualized using magnifying loops at 3X magnification and optical stereomicroscope at 10X magnification. Images were analyzed using AutoCAD 2004 software to calculate area of the remaining debris in the canal. For statistical analysis were used variance test and ANOVA. Results. Total debris/canal area ratio between the three groups showed a statistically significant difference (P < 0.001). Conclusion. ProTaper retreatment system did not produce completely clean canals in any of the groups. However, it had the best efficacy towards removing silicon based obturating material GuttaFlow.